Revolutionizing Senior High School Teaching with Augmented Reality-Based Quantum Training - Siswati, Bea Hana; Wicaksono, Iwan (Universitas Lambung Mangkurat, 2025)
This community service project aims to enhance teachers' pedagogical skills at Rambipuji Jember State High School through training in Quantum Teaching integrated with Augmented Reality (AR). Integrating technology into education is crucial to creating a more interactive and engaging learning environment in today's digital era. Quantum Teaching employs a blend of techniques to boost learning effectiveness, which can deliver a more immersive educational experience when supported by AR technology. The project uses the Participatory Action Research (PAR) method, involving stages that start with an introduction to Quantum Teaching and AR, followed by practical workshops where teachers develop AR-based learning materials aligned with the curriculum. The training also includes evaluation sessions to assess teachers' grasp of the concepts taught. As a result, the teachers' understanding of these innovative teaching methods improved, enabling them to design and implement AR-supported lessons in their respective subjects. This initiative has significantly bolstered the pedagogical competencies of Rambipuji Jember State High School teachers, enhancing the school's capacity to become a model for other institutions in adopting technology-driven teaching strategies. The project's outcomes suggest a broader potential for these approaches to influence educational practices beyond the local context, encouraging continuous advancements in technology-integrated learning.